Nickel Extraction From Solid Waste From The Nickel Smelting Industry Through An Environmentally Friendly Organic Acid Leaching Process - Muh. Isnin Asri; Selfina Gala (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the effect of the type and concentration of organic acids on nickel extraction results. The analysis shows that the type of organic acid has a significant effect on the effectiveness of nickel leaching. Citric acid produces higher extraction yields than acetic acid due to its polyprotic nature, which enables it to form stronger complexes with nickel ions. In addition, the concentration of organic acids plays an important role in the extraction process. The optimum concentration was achieved at 7 M, resulting in the highest nickel percentage of 0.78%. At a concentration of 4 M, the extraction yield was lower due to the limited availability of H⁺ ions, while at 10 M, a decrease in extraction efficiency was observed, which is likely caused by the formation of secondary complexes or precipitates that inhibit nickel solubility. Therefore, the appropriate selection of organic acid type and concentration is crucial for optimizing the nickel extraction process.